1994
DOI: 10.1128/iai.62.2.747-750.1994
|View full text |Cite
|
Sign up to set email alerts
|

Conconavalin A-stimulated bovine T-cell supernatants inhibit growth of Cowdria ruminantium in bovine endothelial cells in vitro

Abstract: Conconavalin A-stimulated bovine T-cell supernatants inhibited the growth of Cowdria ruminantium in bovine endothelial cells in vitro but did not affect their entry. This finding represents one mechanism by which T cells may control C. ruminantium multiplication and hence affect the severity of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…The Con-A T cell supernatants used in this study were those that were used in the previous study (Mahan et al 1994), and were obtained on the third day of Con-A stimulation of peripheral blood leucocytes of an uninfected bovine animal (Mahan et al 1994). The concentration of IFN in the Con A-stimulated bovine T cell supernatant was 272 pg/ml determined by use of a commercially available ELISA (Commonwealth Serum Laboratories, Parkville, Victoria, Australia).…”
Section: Testing the Effects Of Anti-ifng And Anti-tnfa Antisera On Tmentioning
confidence: 99%
See 3 more Smart Citations
“…The Con-A T cell supernatants used in this study were those that were used in the previous study (Mahan et al 1994), and were obtained on the third day of Con-A stimulation of peripheral blood leucocytes of an uninfected bovine animal (Mahan et al 1994). The concentration of IFN in the Con A-stimulated bovine T cell supernatant was 272 pg/ml determined by use of a commercially available ELISA (Commonwealth Serum Laboratories, Parkville, Victoria, Australia).…”
Section: Testing the Effects Of Anti-ifng And Anti-tnfa Antisera On Tmentioning
confidence: 99%
“…Four experimental groups were created each containing five 25 cm 2 flasks of BPA 593/1 endothelial cells. The isolation, propagation and maintenance of these cells has been described previously (Byrom & Yunker 1990, Mahan et al 1994. All endothelial cell cultures were infected with 1 ml supernatant of C. ruminantium Crystal Springs strain organisms from a terminally infected culture as described previously (Mahan et al 1994).…”
Section: Testing the Effects Of Anti-ifng And Anti-tnfa Antisera On Tmentioning
confidence: 99%
See 2 more Smart Citations
“…Cell-mediated immunity can be mediated directly through cell cytotoxic effects and indirectly via the production of cytokines that enable the elimination of intracellular infection (Abbas et al 1994). Cytokines in general (Turco & Winkler 1983a, Wisseman & Waddel 1983, Mahan et al 1994 and interferon (IFN)-gamma in particular, have been shown to exert antirickettsial effects in in vitro (Turco & Winkler 1983a,b, 1989, 1994, Wisseman & Waddel 1983, Manor & Sarov 1990, Gao et al 1993, Feng et al 1994, Mahan et al 1994, 1996 and in vivo (Li et al 1987) studies. The inhibitory effects of IFN-gamma (Totte et al 1993, Mahan et al 1996 and IFN-alpha (Totte et al 1993(Totte et al , 1994 on the growth of C. ruminantium have been demonstrated.…”
Section: Introductionmentioning
confidence: 99%